Axial spondyloarthritis. Issue 12 (6th October 2021) - Navarro-Compán, Victoria; Sepriano, Alexandre; El-Zorkany, Bassel; van der Heijde, Désirée
Abstract : Axial spondyloarthritis (axSpA) encompasses both radiographic and non-radiographic axSpA. It is a chronic inflammatory disease with a predilection for involving the axial skeleton. The most common presenting symptoms are chronic back pain and spinal stiffness but peripheral and extra-musculoskeletal manifestations occur also frequently. The diagnosis of axSpA relies on the recognition of a clinical pattern of the disease, based on clinical, laboratory and imaging features. The Assessment in SpondyloArthritis international Society classification criteria for axSpA are valid and well implemented for research purposes. Sustained disease activity, measured by validated tools such as the Ankylosing Spondylitis Disease Activity Score, leads to irreversible structural damage and poor functioning and therefore should be abrogated. As part of the management algorithm, non-steroidal anti-inflammatory drugs remain as the first line of pharmacological treatment besides physiotherapy. As a second line, tumour necrosis factor inhibitor and interleukin-17 inhibitor are available but recently Janus kinase inhibitors have also shown efficacy in improving symptoms of the disease.